The surface grafting of graphene oxide with poly(ethylene glycol) as a reinforcement for poly(lactic acid) nanocomposite scaffolds for potential tissue engineering applications. (January 2016) - Zhang, Chunmei; Wang, Liwei; Zhai, Tianliang; Wang, Xinchao; Dan, Yi; Turng, Lih-Sheng
Abstract: Graphene oxide (GO) was incorporated into poly(lactic acid) (PLA) as a reinforcing nanofiller to produce composite nanofibrous scaffolds using the electrospinning technique. To improve the dispersion of GO in PLA and the interfacial adhesion between the filler and matrix, GO was surface-grafted with poly(ethylene glycol) (PEG). Morphological, thermal, mechanical, and wettability properties, as well as preliminary cytocompatibility with Swiss mouse NIH 3T3 cells of PLA, PLA/GO, and PLA/GO-g-PEG electrospun nanofibers, were characterized. Results showed that the average diameter of PLA/GO-g-PEG electrospun nanofibers decreased with filler content. Both GO and GO-g-PEG improved the thermal stability of PLA, but GO-g-PEG was more effective. The water contact angle test of the nanofiber mats showed that the addition of GO in PLA did not change the surface wettability of the materials, but PLA/GO-g-PEG samples exhibited improved wettability with lower water contact angles. The tensile strength of the composite nanofiber mats was improved with the addition of GO, and it was further enhanced when GO was surface grafted with PEG. This suggested that improved interfacial adhesion between GO and PLA was achieved by grafting PEG onto the GO. The cell viability and proliferation results showed that the cytocompatibility of PLA was not compromised with the addition of GO and GO-g-PEG. With enhanced mechanical properties as well as good wettability and cytocompatibility, PLA/GO-g-PEG composite nanofibers have the potential to be used as scaffolds in tissue engineering.